1979
DOI: 10.1111/j.1365-2184.1979.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Stem Cell Seeding Efficiency and Position in Cell Cycle

Abstract: The seeding efficiency of colony‐forming cells from normal, regenerating and velocity‐sedimented cycling and non‐cycling narrow preparations was compared. Colony‐forming cells in cycle were found to exhibit a 50% reduction in splenic seeding when compared to normal marrow or sedimented non‐cycling cells. The results of this study indicate that the spleen colony assay underestimates the total number of colony‐forming cells by a fraction which is directly related to the number of cells in cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Similarly BERAN & TRIBUKAIT (1) described a lowering of seeding efficiency of control bone marrow in the spleens of irradiated mice pretreated by prolonged hypoxia, which is known to increase the capacity of self-renewal and generation of descendent cells determined 10 to 14 days later. These observations agree with the suggestion of MONETTE & DEMELLO (12) suggesting that colonyforming cells in cycle exhibit reduced spleen seeding when compared with normal marrow. One can hypothesize that the decrease of seeding efficiency as measured by the double-transplant method at 24 h after the injection of marrow cells is conditioned by the switching of transplanted CFUs into cell cycle induced by the metabolically influenced host environment.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly BERAN & TRIBUKAIT (1) described a lowering of seeding efficiency of control bone marrow in the spleens of irradiated mice pretreated by prolonged hypoxia, which is known to increase the capacity of self-renewal and generation of descendent cells determined 10 to 14 days later. These observations agree with the suggestion of MONETTE & DEMELLO (12) suggesting that colonyforming cells in cycle exhibit reduced spleen seeding when compared with normal marrow. One can hypothesize that the decrease of seeding efficiency as measured by the double-transplant method at 24 h after the injection of marrow cells is conditioned by the switching of transplanted CFUs into cell cycle induced by the metabolically influenced host environment.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, seeding efficiency is affected by the proliferative activity of stem cells. Monette and DeMello 37 showed that cycling spleen colony forming cells show a 50% reduction of their homing efficiency, while more recenty we showed that even a 3-h ex vivo incubation of bone marrow cells resulted in a similar 50% loss of seeding and consequently a 50% reduction of repopulating ability in a mouse model. 36 Stem cells with a stable retroviral vector integration have gone through a proliferative cycle during or shortly after the transfection protocol and consequently may have a seeding disadvantage in vivo as compared to the untransduced cells.…”
Section: Discussionmentioning
confidence: 58%
“…HSCs that are in the G 0 phase of the cell cycle at the time of transplantation promote higher levels of engraftment than HSCs in the G 1 phase 45,46 and especially HSCs in the S phase. 47,48 A greater proportion of HSCs in old mice are cycling, 6 so this difference may underlie their diminished capability for homing. Third, it is possible there is an age-related change in radiosensitivity of HSCs manifested in the present experiments by differential ablation of host HSCs and thus a differential probability with which transplanted HSCs may find unoccupied niches.…”
Section: Discussionmentioning
confidence: 99%